The past, the present and the future of #UroSoMe: A narrative review - TANIDIR, YILÖREN (My University, 2021)
© AME Medical Journal. All rights reserved.The professional use of Social Media (SoMe) in medicine has dramatically increased in the last decade, particularly in urology. SoMe platforms permit medical education, facilitate provider network, and promote scientific knowledge and multi-institution collaborations. However, their inappropriate use may lead to ethical and privacy conflicts. In 2018, Jeremy Y. C. Teoh (@jteoh_hk) created a hashtag specific to urology: #UroSoMe. The first official invitation to engage in #UroSoMe was sent out in Twitter in December 2018 and this is considered the birth of the #UroSoMe community. In the present paper, we reviewed several and important aspects of the use of SoMe in urology. The pro and cons of SoMe, the history and achievements of the #UroSoMe group, the guidelines in SoMe in urology and the future development of professional use of SoMe were deeply covered.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; #UroSoMe; internet; Social Media (SoMe); Twitter messaging; urology